Specifics of military leadership - Hatidža Beriša; Barišić Igor (Megatrend Revija)
The paper starts from consideration of the theoretical basis of leadership, as well as its relationship with management as a basic approach in managing the organization, in order to arrive at a certain definition of military leadership. Leadership exists as long as man himself, throughout history it has been instinctively understood and experienced almost as a natural phenomenon. There were always leaders and every activity of a group of people was led by someone. Leadership came into the focus of the scientific community, as a subject worth studying, only at the beginning of the 20th century. Through more than a century, until today, definitions of leadership have changed, evolved and been conditioned by a large number of factors, ranging from the dominant philosophy of the historical moment to the point of view of the scientific discipline for whose needs leadership is defined. Through paper, the authors strive to single out the basic characteristics of the military organization and military calling and look at their influence on leadership in the military context. The focus of the research is to highlight the characteristics of the extreme military environment and identify the essential characteristics of military leadership in such extreme dangerous conditions. The goal of the paper is to comprehensively look at the essential characteristics of military leadership, while respecting the fact that it is about specifics, and not about a new, fundamentally different approach to leadership and management compared to civilian organizations. Pointing to the specifics of the military call, the unjustification of the tendency to equate the military profession with other less dangerous and riskier occupations is highlighted, which also reflects the social importance of paper.